Harbingers of modernity: Monetary injections and European economic growth, 1492-1790 - Nuno Palma (European Historical Economics Society (EHES), 2017)
PhD dissertation summary forthcoming at: European Review of Economic History
Keywords: E40; E50; N13; O40; 330; Early modern monetary injections; liquidity effects; monetary non- neutralities; historical money supply; economic growth